ORGANOLEPTIC VALUE OF BALI BEEF MARINATED WITH TRIGONA HONEY - D., RAMADHANI; SRIYANI, N. L. P.; DEWANTARI, M. (Majalah Ilmiah Peternakan; Vol 27 No 1 (2024): Vol. 27 No. 1 (2024), 2024)
This’ research aims’ to’ determine’ the’ best effect’ and’ assess the’ organoleptic’ value of’ Bali’ beef after marina- tion using Trigona honey. The meat marination process was’ carried’ out’ for 30’ minutes’ at’ room’ temperature’. The’ research design’ used’ was a’ Completely’ Randomized’ Design’ (CRD) with’ four’ treatments’ and’ seven replica- tions’. The’ four treatments’ included non-marinated meat’ (P0), meat’ marinated’ with’ 5 ml of Trigona honey (P1), meat marinated with 10 ml of Trigona honey (P2), and meat marinated with 15 ml of Trigona honey (P3). The’ vari- ables’ observed’ in’ the study’ included’ color’, aroma’, taste, texture’, tenderness, and’ overall acceptance evaluated by 15 semi-trained panelists. The results showed that marinating Bali beef with Trigona honey significantly influen- ced color, aroma, taste, tenderness, and overall acceptance, but’ did’ not’ have’ a’ significant’ effect’ on’ texture. The’ conclusion’ of this’ study’ is’ that’ the best marination for Bali beef is achieved using Trigona honey at a level of 10 ml, as indicated by the increased values of aroma, taste, texture, tenderness, and overall acceptance by the panelists.